2010
DOI: 10.1007/s11071-010-9784-5
|View full text |Cite
|
Sign up to set email alerts
|

Control of vibroimpact dynamics of a single-sided Hertzian contact forced oscillator

Abstract: The control of vibroimpact dynamics of a single-sided Hertzian contact forced oscillator is investigated analytically and numerically in this paper. The control strategy is introduced via a fast excitation and attention is focused on the response near the primary resonance. The fast excitation is added to the basic harmonic force, either through a harmonic force applied from above, or via a harmonic base displacement added from bellow, or by considering the stiffness of the oscillator as a periodically and rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Considering the contact between the stator and the rotor, and the nonlinearity of the piezoceramic material, a single-sided Hertzian-contact forced oscillator model can be employed to represent this system [ 32 ]. The TRUM could be modeled as a spring-mass-damper-lumped system of a single degree of freedom with a nonlinear spring arranged in parallel, as shown in Figure 8 .…”
Section: Modeling and Identificationmentioning
confidence: 99%
“…Considering the contact between the stator and the rotor, and the nonlinearity of the piezoceramic material, a single-sided Hertzian-contact forced oscillator model can be employed to represent this system [ 32 ]. The TRUM could be modeled as a spring-mass-damper-lumped system of a single degree of freedom with a nonlinear spring arranged in parallel, as shown in Figure 8 .…”
Section: Modeling and Identificationmentioning
confidence: 99%
“…Some methods of controlling this vibro-impact response were presented by Bichri and Belhaq 24 and Bichri et al. 25,26 The presented control methods utilized fast harmonic load/displacement, fast harmonic modulation of contact stiffness, or introduction of electromagnetic actuator. Xiao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hertzian contact nonlinearity is one of the primary reasons for the nonlinear jump phenomenon. Some methods of controlling this vibro-impact response were presented by Bichri and Belhaq 24 and Bichri et al 25,26 The presented control methods utilized fast harmonic load/ displacement, fast harmonic modulation of contact stiffness, or introduction of electromagnetic actuator. Xiao et al 27 used the MMS and HBM and exact method to determine the natural frequency of a mass with Hertzian contact stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Based on numerical simulations, analytical approximation and experimental testing [3,4], it was concluded that the loss of contact is generally initiated by jumps near the resonances. In order to control the location of such jumps, three strategies were developed recently [5,6]. The first strategy introduced a fast harmonic excitation added to the basic harmonic forcing from above, the second used a fast harmonic base displacement, while the third one considered a rapidly harmonic parametric stiffness.…”
Section: Introductionmentioning
confidence: 99%